Lifetime of sessile saliva droplets in the context of SARS-CoV-2. (April 2021) - Balusamy, Saravanan; Banerjee, Sayak; Sahu, Kirti Chandra
Abstract: Spreading of respiratory diseases, such as COVID-19, from contaminated surfaces is dependent on the drying time of the deposited droplets containing the virus. The evaporation rate depends on environmental conditions, such as ambient temperature and relative humidity and physical properties (e.g., droplet volume, contact angle and composition). The respiratory droplets contain salt (NaCl), protein (mucin), and surfactant (dipalmitoylphosphatidylcholine) in addition to water, which are expected to influence the evaporation in a big way. A diffusion-based theoretical model for estimating the drying time is developed which takes into account the dynamic contact angle of saliva droplets laden with salt and insoluble surfactants. The effect of the initial volume, contact angle, salinity, surfactant concentration, ambient temperature and relative humidity on the drying time of droplets is investigated. Graphical abstract: Unlabelled Image Highlights: Drying time of sessile saliva droplets in the context of SARS-CoV-2 is calculated. A diffusion-based theoretical model is developed which takes into account the dynamic contact angle of saliva droplets. Saliva droplets contain water, salt, mucin and dipalmitoylphosphatidylcholine (surfactant). Our results show nonlinear evaporation dynamics affected by the presence of surfactants. Effect of these parameters on the drying time of droplets is investigated.